HIV-1 infected humanized DRAGA mice develop HIV-specific antibodies despite lack of canonical germinal centers in secondary lymphoid tissues - Ollerton, Matthew T.; Folkvord, Joy M.; Peachman, Kristina K.; Shashikumar, Soumya; Morrison, Elaine B.; Jagodzinski, Linda L.; Peel, Sheila A.; Khreiss, Mohammad; D’Aquila, Richard T.; Casares, Sofia; Rao, Mangala; Connick, Elizabeth (Frontiers in Immunology, 2022)
A major barrier in the use of humanized mice as models of HIV infection is the inadequate generation of virus-specific antibody responses. Humanized DRAGA (hDRAGA) mice generate antigen-specific class switched antibodies to several pathogens, but whether they do so in HIV-1 (HIV) infection and the extent to which their secondary lymphoid tissues support germinal center responses is unknown. hDRAGA mice were evaluated for their ability to support HIV replication, generate virus-specific antibody responses, develop splenocyte subsets, and organize secondary lymphoid tissue architecture. hDRAGA mice supported persistent HIV replication and developed modest levels of gp41-specific human IgM and IgG. Spleens from uninfected and HIV infected hDRAGA mice contained differentiated B and CD4+ T cell subsets including germinal center (GC) B cells and T follicular helper cells (TFH); relative expansions of TFH and CD8+ T cells, but not GC B cells, occurred in HIV-infected hDRAGA mice compared to uninfected animals. Immunofluorescent staining of spleen and lymph node sections demonstrated atypical morphology. Most CD4+ and CD8+ T cells resided within CD20hi areas. CD20hi areas lacked canonical germinal centers, as defined by staining for IgD-Ki67+ cells. No human follicular dendritic cells (FDC) were detected. Mouse FDC were distributed broadly throughout both CD20hi and CD20lo regions of secondary lymphoid tissues. HIV RNA particles were detected by in situ hybridization within CD20+ areas and some co-localized with mouse FDC. Viral RNA+ cells were more concentrated within CD20hi compared to CD20lo areas of secondary lymphoid tissues, but differences were diminished in spleen and eliminated in lymph nodes when adjusted for CD4+ cell frequency. Thus, hDRAGA mice recapitulated multiple aspects of HIV pathogenesis including HIV replication, relative expansions in TFH and CD8+ T cells, and modest HIV-specific antibody production. Nevertheless, classical germinal center morphology in secondary lymphoid tissues was not observed, which may account for the inefficient expansion of GC B cells and generation of low titer human antibody responses to HIV-1 in this model.